Interleukin-17A promotes functional activation of systemic sclerosis patient-derived dermal vascular smooth muscle cells by extracellular-regulated protein kinases signalling pathway - Liu, Mengguo; Yang, Ji; Xing, Xiaojing; Cui, Xiangxiang; Li, Ming (Arthritis research & therapy, 2014)
Dermal vascular smooth muscle cells (DVSMCs) are important for vascular wall fibrosis in microangiopathy of systemic sclerosis (SSc). T helper 17 cell-associated cytokines, particularly interleukin-17A (IL-17A), have been demonstrated to play a role in the pathogenesis of SSc. However, the effect of IL-17A on the DVSMCs in microangiopathy of SSc has not been established. In the present study, we investigated the effect of IL-17A on the SSc patient-derived DVSMCs. DVSMCs from patients with SSc and healthy subjects were incubated using IL-17A or serum derived from patients with SSc. Subsequently, the proliferation, collagen synthesis and secretion, and migration of DVSMCs were analysed using a cell counting kit-8 (CCK-8), dual-luciferase reporter assay, real-time reverse transcription-polymerase chain reaction (RT-PCR), Western blot, enzyme-linked immunosorbent assay (ELISA) and transwell assay. The protein phosphorylation of signalling pathways in the process of IL-17A-mediated DVSMC activation was investigated and validated by specific signalling pathway inhibitor. IL-17A and serum from patients with SSc could promote the proliferation, collagen synthesis and secretion, and migration of DVSMCs. IL-17A neutralising antibody could inhibit the IL-17A-induced activation of DVSMCs. Additionally, IL-17A induced the activation of extracellular-regulated protein kinases 1/2 (ERK1/2) in DVSMCs, and ERK1/2 inhibitor could block the IL-17A-elicited activation of DVSMCs. Our results suggested that IL-17A derived from patients with SSc might induce the proliferation, collagen synthesis and secretion, and migration of DVSMCs via ERK1/2 signalling pathway, raising the likelihood that IL-17A and ERK1/2 might be promising therapeutic targets for the treatment of SSc-related vasculopathy.